World heritage listing as a catalyst for collaboration: can Mount Fuji's trail signs point the way for Japan's multi-purpose national parks?. Issue 3 (3rd July 2018) - Jones, Thomas; Beeton, Sue; Cooper, Malcolm
ABSTRACT: Iconic Mount Fuji has symbolized the fragmented state of Japan's 'multi-purpose' national park administration. Although the Ministry of Environment (MOE) is the legal administrator, the national parkland is predominantly owned by the Forestry Agency, with many services provided by local governments. This complex combination can result in stakeholders pitted against each other, but listing as a World Heritage Site (WHS) offers an external incentive toward holistic management. This paper reviews Fuji's 2013 WHS inscription process, analyzing official documents and a series of stakeholder interviews to substantiate claims that it helped catalyze stakeholder collaboration, as demonstrated by a new system of trail signs. A cross-cutting council formed in 2009 issued a set of guidelines aimed at standardization of place names, and the removal of unnecessary or low-quality signs. Subsequently, a simplified system of color-coded signs was introduced along the four climbing trails, epitomizing the new spirit of cooperation. However, more research is needed to verify if the new partnership can extend the collaboration from trail signs to incorporate broader provision of visitor services, and now that the 'carrot' of inscription has been achieved, the multi-stakeholder momentum may be difficult to maintain.